Low-velocity Precessing Jets Can Explain Observed Morphologies in the Twin Radio Galaxy TRG J104454+354055 - Santanu Mondal; Gourab Giri; Ravi Joshi; Paul J. Wiita; Gopal-Krishna; Luis C. Ho (The Astrophysical Journal)
Our understanding of large-scale radio jets in merger systems has been drastically improved in the era of the Very Large Array, Very Long Baseline Array/European VLBI Network, upgraded Giant Metrewave Radio Telescope, and MeerKAT. Twin radio galaxies (TRGs) are rare interacting galaxy pairs where both supermassive black holes host kiloparsec-scale bipolar radio jets. Only recently was a third TRG discovered, and it shows significantly different jet morphologies than the previous two. Due to both the extreme paucity and complexity of such systems, the launching of their jets as well as their mutual interaction during the propagation through the ambient medium are not well understood. We have performed three-dimensional hydrodynamic simulations to study the bipolar jets in the third TRG, J104454+354055. Our study indicates that the precession of mutually tilted bipolar jets originating from the two galactic nuclei separated by tens of kiloparsecs and propagating at low velocities can explain the observed morphologies. The simulated jet precession timescales are short compared to the overall dynamical timescale of the jets, and could originate from Lense–Thirring effect in the accretion disks. This approach to understanding TRG jet dynamics could also be applied to other TRG systems with similar helical morphologies that may be discovered in the upcoming era of the Square Kilometre Array and its pathfinder surveys.